REPOSITIONING THE INDONESIAN CREDIT CARD INDUSTRY IN THE ERA OF DIGITAL FINANCIAL SERVICES: A SCENARIO PLANNING APPROACH - Fabian Dheano Alamsyah; Yos Sunitiyoso (RADJA PUBLIKA, 2026)
This study aims to analyze the current position of the Indonesian credit card industry in formulating alternative scenario planning as a repositioning effort in the digital era. Using a qualitative research design with descriptive methods, this study was conducted using interview data collection and documentation studies from various literature sources. Scenario planning was developed using PESTEL analysis and Porter’s Five Forces to identify key points, changes, and future scenario planning for credit cards in Indonesia. The results indicate that efforts to reposition the Indonesian credit card industry require strengthening and integrating the Indonesian credit card industry ecosystem with digitalized services. Transformation efforts are not limited to just transformation efforts, but also the need to strengthen regulators that offer customer acquisition and expand flexible collaboration